RELATIONSHIP OF PHYSICAL ACTIVITY WITH BODY MASS INDEX AND LIPID PROFILE OF FIRST YEAR OF MEDICAL STUDENTS FACULTY OF MEDICINE UNIVERSITY OF MATARAM - Ida Ayu Eka Widiastuti (Unram Medical Journal, 2022)
Background: Physical activity can improve physical fitness. By maintaining a good level of physical fitness not only prevent an increase in body fat percentage, but also improve lipid profiles. Elevated value of total cholesterol and low-density lipoprotein cholesterol (LDL-C) with low levels of high-density lipoprotein cholesterol (HDL-C) are an important risk factors for coronary heart disease, in addition to above-normal body mass index, both overweight and obesity. The purpose of this study was to determine the relationship between physical activity and body mass index, lipid profile of first year students of Medical Students Faculty of Medicine, University of Mataram. Method: The research subjects were 93 first year students. Physical activity level was measured using the IPAQ-SF (International Physical Activity-Short Form) questionnaire, body mass index (BMI) by dividing body weight (kg) by height (m2) and examination of lipid profiles which included: triglyceride, total cholesterol , HDL and LDL cholesterol from blood serum using enzymatic colorimetric method. Data were analyzed statistically by Spearman correlation test. Results: The results showed that there was no significant correlation between the level of physical activity with BMI, cholesterol, triglyceride, and LDL value, with significance values (p) respectively: 0.162, 0.14, 0.327, 0.51. There was a significant correlation between level of physical activity and HDL (p=0.018; r=0.242). Conclusion: Body mass index and lipid profile are not only affected by the level of physical activity. The higher the level of physical activity, the better HDL levels